2020
DOI: 10.1136/archdischild-2019-318080
|View full text |Cite
|
Sign up to set email alerts
|

The practice of blood volume submitted for culture in a neonatal intensive care unit

Abstract: BackgroundNeonatal sepsis is the leading cause of mortality and morbidity in neonatal intensive care units. The volume of blood taken for culture remains one of the most important factors in isolating microorganisms.ObjectivesTo evaluate the impact of the intervention on the blood volume submitted for culture and to identify factors influencing the volume as determined by the phlebotomist.MethodsBlood culture volume was determined by weighing the culture bottle before and immediately after blood inoculation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…At the other end of the age spectrum, two interventional studies have shown that it is possible to make significant improvements in the NNU median volume submitted, with our post-intervention median of 0.95 ml in line with other reports [ 33 , 34 ]. In combination with a feasibility study [ 35 ], these studies show it is generally possible to obtain 1 ml even in the smallest infants, and we plan to emphasize this higher threshold in our guidance update.…”
Section: Discussionsupporting
confidence: 91%
“…At the other end of the age spectrum, two interventional studies have shown that it is possible to make significant improvements in the NNU median volume submitted, with our post-intervention median of 0.95 ml in line with other reports [ 33 , 34 ]. In combination with a feasibility study [ 35 ], these studies show it is generally possible to obtain 1 ml even in the smallest infants, and we plan to emphasize this higher threshold in our guidance update.…”
Section: Discussionsupporting
confidence: 91%
“…This concern is not speculative because surprisingly low inoculant volumes have been reported by several studies. 22 , 23 The efficacy of real-time bedside verification of blood volumes sent for culture may cause negative culture results to be more trustworthy. Thus, patients treated during the post-intervention period of this study were more likely to be administered antibiotics for <72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Several reports of formal quality initiatives focused on NICU blood culturing have shown that such efforts can improve beside processes, reduce blood culture contamination, increase sample volumes, and minimize error in a sustainable way regardless of the level of neonatal care. 9,26,27 No single national standard that addresses all meaningful components of blood drawing, training, and contamination reporting in the NICU is available. Such a document would be a useful tool for this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%